2012
DOI: 10.5755/j01.ms.18.2.1921
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Thermal Properties of Double-Layered Weft Knitted Fabrics

Abstract: It is known, that fibre type, yarn properties, fabric structure, finishing treatments and clothing conditions are the main factors affecting thermo-physiological comfort. The warmth of a fabric is due to insulation provided by air trapped between fibres and yarns. Fabrics from straight filament yarns remove heat rapidly by conduction when placed next to the skin and in such a way produce a so-called cool feel or handle. The objects of investigation were double-layered weft fabrics knitted from cotton or man-ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 2 publications
1
38
0
Order By: Relevance
“…They concluded that single jersey fabric takes longer to absorb water droplet as compared with single pique fabrics. It was observed that thick knitted fabric gave warmer sense [14]. Moreover, it was found after a comparative study of different knitted structures that the open construction 3D eyelet fabric has better water vapour permeability than that of micromesh, pique and mock rib structure [15].…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that single jersey fabric takes longer to absorb water droplet as compared with single pique fabrics. It was observed that thick knitted fabric gave warmer sense [14]. Moreover, it was found after a comparative study of different knitted structures that the open construction 3D eyelet fabric has better water vapour permeability than that of micromesh, pique and mock rib structure [15].…”
Section: Introductionmentioning
confidence: 99%
“…One layer (outer) was made from cotton yarns or man-made bamboo yarns and the (inner) was from synthetic fiber yarns (polypropylene, polyester and polyamide). The focal point of their research was to investigate the influence of knitting structure, fiber type, and yarn properties on the air and water vapor permeability of double-layered weft knitted fabrics [6]. Greyson and Havenith mentioned that heat and water vapor resistance increases with the increasing of thickness and air trapped in the fabric [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have considered the fabric density, thickness and weight of the fabric, for which correlations have been made with air permeability, whiteness and the ability to manage the transport index to determine the performance of the knitted products [5][6][7][8]. Double layer composite knits have been investigated to find a statistical model for prediction purposes [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…From the point of view of the fibrous composition of the knitted fabrics used, in this research, took knitted fabrics from wool, cotton, bamboo and synthetic (polyester), artificial (viscose) were measured and comparatively analyzed. Knitted composites from polyester fibers yarns in inner layer are combined with cotton or bamboo threads in outer layer, to show comfort benefits due to higher thickness [4,[10][11][12].…”
Section: Introductionmentioning
confidence: 99%